2017
DOI: 10.3892/ijmm.2017.2890
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin regulates astrocyte migration and proliferation in vitro

Abstract: Fisetin (3,3′,4′,7-tetrahydroxyflavone) is a plant flavonol found in fruits and vegetables that has been reported to inhibit migration and proliferation in several types of cancer. Reactive astrogliosis involves astrocyte migration and proliferation, and contributes to the formation of glial scars in central nervous system (CNS) disorders. However, the effect of fisetin on the migration and proliferation of astrocytes remains unclear. In this study, we found that fisetin inhibited astrocyte migration in a scra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The scratch assay demonstrated that the migration of IEC-18 decreased depending on the NP of 10 8 , 10 9 , or 10 10 Mi-Exo, as compared to the untreated group (80.8 ± 2.5%, 59.1 ± 11.2%, and 22.5 ± 10.9% closing effect, respectively), after Mi-Exo treatment for 24 h. There is recent evidence that controlled cell migration corresponds to minimizing the extent of scar formation. 30 It might be assumed that the anti-cell migration activity can be induced by the expression level of TGFβ isoforms. Relative TGF-β1 and TGF-β3 mRNA levels were quantified, and compared by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…The scratch assay demonstrated that the migration of IEC-18 decreased depending on the NP of 10 8 , 10 9 , or 10 10 Mi-Exo, as compared to the untreated group (80.8 ± 2.5%, 59.1 ± 11.2%, and 22.5 ± 10.9% closing effect, respectively), after Mi-Exo treatment for 24 h. There is recent evidence that controlled cell migration corresponds to minimizing the extent of scar formation. 30 It might be assumed that the anti-cell migration activity can be induced by the expression level of TGFβ isoforms. Relative TGF-β1 and TGF-β3 mRNA levels were quantified, and compared by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of scratch-wound assays is often done by microscopic measurement at one defined time point [93,[95][96][97]. For the present study, a new protocol was developed using the possibilities of live cell microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previously demonstrated pro‐neurogenesis effects of fisetin in the hippocampus (Wang et al . ), we found that fisetin increased the activation of TrkB signaling in the hippocampus (Fig. ).…”
Section: Discussionmentioning
confidence: 56%